Evolution of blood–brain barrier damage associated with changes in brain metabolites following acute ischemia. Issue 16 (11th November 2015) - Yan, Gen; Xuan, Yinghua; Dai, Zhuozhi; Zhang, Guishan; Xu, Haiyun; Mikulis, David; Wu, Renhua
<x xml:space="preserve">Abstract</x> Stroke is a serious medical condition that requires emergency care. In the case of ischemic stroke, ischemia may lead to damage to the blood–brain barrier (BBB); the damage in turn may exacerbate the condition. Therefore, noninvasive detection of BBB damage represents a challenge for experimental and clinical researchers. In this study, we assessed the onset of BBB disruption by means of T1-weighted images with administration of the contrast enhancement agent gadolinium-diethylenetriamine pentaacetic acid (Gd-DTPA) and related BBB breakdown to brain metabolite changes in proton magnetic resonance spectrum (1H-MRS) in the infarcted site following middle cerebral artery occlusion (MCAO) in rats. It was shown that MCAO for 30 min and 1.5 h caused no Gd-DTPA signal change in the T1-weighted images, whereas MCAO for 1 h significantly altered some of 1H-MRS brain metabolites, suggesting that brain metabolite changes occurred earlier than BBB damage after ischemic stroke. MCAO for 2 h caused BBB breakdown, which was related to changes in the levels of some brain metabolites detected by 1H-MRS. Between the second and the third hour after MCAO, brain metabolite changes continued as the result of BBB breakdown and the concurrent overperfusion to the infarcted site, which may ameliorate the metabolite changes, thus compensating for the functional failures of the brain after stroke.